Developing Pancasila education e-module using Panrita Lopi context and Wordwall media to foster the fifth graders’ learning motivation and national character - Andi Arbaina Fariza; Muhammad Nawir; Abdul Azis (Universitas Ahmad Dahlan, 2026)
The Pancasila education e-module based on Panrita Lopi culture integrated with Wordwall media was developed to strengthen students' motivation and national character. Pancasila education is a subject that teaches Indonesia’s national ideology called Pancasila, while Panrita Lopi refers to a local maritime cultural value emphasizing wisdom and craftsmanship in boat-making from South Sulawesi. This study aims to (1) develop the e-module, (2) analyze its validity, (3) analyze its practicality, and (4) analyze its effectiveness on students' motivation and national character. The method used is Research and Development (R&D) with the ADDIE development model developed by Dick and Carey, involving 29 fifth-grade students of SD Negeri 27 Matekko. The developed e-module features interactive learning content, cultural contextualization, and game-based evaluation through Wordwall media. The results indicate that the e-module is highly feasible, practical, and effective for use in learning. This is evidenced by validation results from media, material, and cultural experts, each obtaining a score of 100% (very valid). Practicality is shown by teacher responses (99%) and student responses (97%), as well as motivation (97) and national character (95) in very good categories. Effectiveness is demonstrated by an increase in pretest scores (77) to posttest (94), normal data distribution, and paired sample t-test results (sig. 0.001 < 0.05), indicating H₀ is rejected and Hₐ is accepted. The N-Gain result (0.7107 > 0.70) is categorized as very effective. Thus, the e-module is valid, practical, and effective, and significantly improves students' motivation and national character.